Representasi Nilai-Nilai Budaya Tionghoa dalam Film Karate Kid Legends - Calista Lukito; Zinggara Hidayat (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2026)
This study examines the manifestation of Confucian philosophy within the cinematic narrative of Karate Kid Legends (2025) through the triadic analytical framework of Charles Sanders Peirce’s semiotics, integrated with Asian Communication Theory. Cinema is positioned as a cultural artifact that constructs social reality through a systematic weave of visual, auditory, and narrative signs. Utilizing a qualitative descriptive method, this research identifies the functional relationship between icons, indexes, and symbols across a series of pivotal scenes, interpersonal dialectics, and symbolic gestures. The analysis reveals that the film constructs patterns of hierarchical communication emphasizing moral authority, high-context interactions that remain implicit, and a relational orientation prioritizing collective stability. Furthermore, mechanisms of reputation protection (face saving) and strategies of direct confrontation avoidance emerge as derivations of the universal principle of harmony. These values are firmly internalized within the dynamics of the mentor–disciple relationship, familial authority structures, and the methodology of self-discipline that serves as the story's axis. These findings confirm that the audiovisual work fulfills a dual function: as a creative industrial product and as an arena for negotiating Chinese cultural identity transforming amidst the dialectic of Eastern and Western societies. Through the representations presented, the film demonstrates that traditional ethics maintain a persistent relevance in mediating social interactions within the modern era.